2010
DOI: 10.1016/j.molimm.2010.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Cell lineage tracing reveals the plasticity of the hemocyte lineages and of the hematopoietic compartments in Drosophila melanogaster

Abstract: Title: Cell lineage tracing reveals the plasticity of the hemocyte lineages and of the hematopoietic compartments in Drosophila melanogaster. Drosophila is a result of a precisely regulated succession of intracellular and intercellular events, though the nature and extent of these interactions are not known. We describe here a cell lineage tracing system set up to analyze the development of hemocyte lineages and functionally distinct hemocyte subsets. This system allowed us to distinguish two major embryonic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(157 citation statements)
references
References 27 publications
8
149
0
Order By: Relevance
“…Many studies established that plasmatocytes and lamellocytes follow specific differentiation pathways (Lanot et al, 2001;Sorrentino et al, 2002Sorrentino et al, , 2004Meister, 2004;Crozatier et al, 2004;Krzemień et al, 2007). However, recent works on Drosophila hemocytes lineage showed that plasmatocytes could indeed differentiate into lamellocytes (Honti et al, 2010;Avet-Rochex et al, 2010;Stofanko et al, 2010). Despite lamellocytes having long been considered the major hemocyte type forming the bulk of capsules in Drosophila (Brehélin and Duvic, 1999), we have shown that not all Drosophila species actually possess this cell type (Eslin and Doury, 2006;Eslin et al, 2009;Havard et al, 2009).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Many studies established that plasmatocytes and lamellocytes follow specific differentiation pathways (Lanot et al, 2001;Sorrentino et al, 2002Sorrentino et al, , 2004Meister, 2004;Crozatier et al, 2004;Krzemień et al, 2007). However, recent works on Drosophila hemocytes lineage showed that plasmatocytes could indeed differentiate into lamellocytes (Honti et al, 2010;Avet-Rochex et al, 2010;Stofanko et al, 2010). Despite lamellocytes having long been considered the major hemocyte type forming the bulk of capsules in Drosophila (Brehélin and Duvic, 1999), we have shown that not all Drosophila species actually possess this cell type (Eslin and Doury, 2006;Eslin et al, 2009;Havard et al, 2009).…”
Section: Introductionmentioning
confidence: 59%
“…Cell lineage analysis demonstrated that embryo-derived plasmatocytes can differentiate into lamellocytes in response to a genetic mutation (Avet-Rochex et al, 2010). Honti et al, 2010 also observed hemocytes with a phagocytic ability expressing lamellocytes markers. More remarkably their study on immunocytes' development showed that hemocytes fate involves a multilineage origin and S. Havard et al / Developmental and Comparative Immunology xxx (2011) xxx-xxx 5 far more plasticity than originally suspected.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies have uncovered unexpected plasticity in hematopoietic development (Avet-Rochex et al 2010;Honti et al 2010;Stofanko et al 2010;Kroeger et al 2012). Wasp infection induces proliferation and lamellocyte differentiation (Sorrentino et al 2002;Krzemien et al 2010b), but infection reduces the abundance of crystal cells (Krzemien et al 2010b).…”
Section: Dual and Reciprocal Non-autonomous Effects Of N On Lineage Dmentioning
confidence: 99%
“…Together, they number ~700 cells by the end of embryogenesis and persist into larval stages, when they undergo multiple rounds of mitosis, generating 6000-8000 hemocytes by the end of larval development Tokusumi et al, 2009b). A subpopulation of these cells will take up residence as sessile hemocytes in subepidermal locations within larvae, where they can be rapidly converted into lamellocytes, a third hemocyte type that is produced in response to wasp infestation (Markus et al, 2009;Honti et al, 2010). Lamellocytes are large, flat, adhesive cells that are crucial for the successful encapsulation of invasive species, such as the parasitic wasp egg.…”
Section: Introductionmentioning
confidence: 99%